A health-related study from food online reviews. The case of gluten-free foods - Pérez-Pérez, Martín (2021)
Concerning the field of Health Sciences, one of the trends with the greatest impact today is related to the feeding and consumption of foods intended for chronic patients with a nutritional association. According to this, the gluten-free diet is one of the diets with a today's fastest-growing due to their health therapy associations for different diseases and because of more and more people are freely choosing to follow a gluten-free diet. On this subject, e-commerce platforms are destined to be a key point for the sale of this kind of products due to: (i) the change in the business model caused by the electronic platforms and (ii) the expected increase consumption of disease designed special foods. For this reason, the experiences written by chronic disease patients and consumers in these platforms have become increasingly relevant. In this sense, the present work applies biomedical text mining methods and demographic knowledge inference techniques to a large number of gluten-free foods consumer's experiences to discover a wide range of health-related topics associated to gluten-free products, alimentary social trends and demographics differences. The results of these analyses show significant trends over time; differences between males and females consumption and a wide range of health-related conclusions, such as: why consumers start a free gluten diet or what are the most discussed diseases and adverse reactions related to these products.